ANALISIS KEMAMPUAN DAYA TAHAN V02 MAX PEMAIN SEPAK BOLA DI KLUB BENGKULU MUDA FC KOTA BENGKULU - Nikentry, Nikentry; Sumantri, Ajis; Juwita, Juwita (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the VO2 Max Endurance Ability of Football Players at Bengkulu Muda Fc Club, Bengkulu City. This type of research is qualitative descriptive research. The research sample amounted to 25 people. The instrument used in this research is the Bleep Test / Multi-Stage. Where the results of the VO2 Max Endurance Ability of Football Players at Bengkulu Muda Fc Club, Bengkulu City in this study show the classification